2019
DOI: 10.1136/bjsports-2019-101365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of youth sports specialisation on career and task-specific athletic performance: a systematic review following the American Medical Society for Sports Medicine (AMSSM) Collaborative Research Network’s 2019 Youth Early Sport Specialisation Summit

Abstract: ObjectiveThe impact, positive or negative, of youth sport specialisation (YSS) on short-term and long-term performance is not fully understood; however, the desire to maximise performance goals is generally considered the primary reason children and adolescents specialise at a young age. We performed a systematic review of original research to establish the association of YSS and task-focused or career-focused performance outcomes.DesignSystematic review.Data sourcesDatabases searched include PubMed, EMBASE, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
0
40
1
7
Order By: Relevance
“…Conceptually, reported experiences of both groups corresponded to the "early diversification" pathway reflected in the DMSP 18 , characterized by sampling different sports during the early years of athletic development and involvement in both FAL and ICL play and practice activities 18,41 . This pathway has been associated with several benefits, including a well-documented reduced health-related risk (later emergence of overuse injuries) 17,42,43 and hypothesized positive effects on prolonged engagement, enjoyment, reduced burnout, healthy psychological and social development 15,18,41,44 . These ideas are clearly aligned with theoretical proposals that talent development in young sport participants is predicated on two phases: one of early enrichment of athletic capacities before the secondary specialization period of dedicated practice in a target sport 19,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, reported experiences of both groups corresponded to the "early diversification" pathway reflected in the DMSP 18 , characterized by sampling different sports during the early years of athletic development and involvement in both FAL and ICL play and practice activities 18,41 . This pathway has been associated with several benefits, including a well-documented reduced health-related risk (later emergence of overuse injuries) 17,42,43 and hypothesized positive effects on prolonged engagement, enjoyment, reduced burnout, healthy psychological and social development 15,18,41,44 . These ideas are clearly aligned with theoretical proposals that talent development in young sport participants is predicated on two phases: one of early enrichment of athletic capacities before the secondary specialization period of dedicated practice in a target sport 19,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of this type of general feedback, especially positive feedback, has been deemed useful to create positive learning environments (Mouratidis et al, 2008). Also, the use of positive feedback is in line with the long-term training principles described by Jayanthi et al (2013) and Kliethermes et al (2020), as well as, it is noted in the soccer related studies by Ford and Williams (2012) and Haugaasen et al (2014). Studies carried out in other sports have also shown the importance of feedback.…”
Section: Discussionmentioning
confidence: 60%
“…1–4 While the intentions may be to increase the chances of future athletic success, evidence suggests that realisation as an adult is not linked to achievement in youth. 5,6 Numerous studies have also reported links between youth who specialise in a single sport and negative long-term outcomes including burnout, sport cessation and increased injury risk. 79 The underlying mechanisms to explain the reasons for these negative consequences associated with sport specialisation remain unclear.…”
Section: Introductionmentioning
confidence: 99%